Electro-catalytic performance of Pd decorated Cu nanowires catalyst for the methanol oxidation. (19th February 2015) - Ren, Yanbiao; Zhang, Shichao; Lin, Ruoxu; Wei, Xin
Abstract Binary shell–core structured electro-catalysts have attracted great attention owing to their superior catalytic performance and low material costs with respect to those monometallic catalysts. A novel Pd decorated copper nanowires (Pd@CNWs) electro-catalyst has been fabricated through the facile hydrometallurgy approach. Pd shells with a thickness of 30–50 nm are uniformly deposited onto the as-prepared CNWs surface, in which ultra-long CNWs (with an average diameter and length of 100 ± 20 nm and 35 ± 5 μm) are used as the one dimensional skeleton as well as reduction agent. Pd@CNWs catalyst exhibits higher catalytic activity and better durability for the methanol electro-oxidation (MEO) in comparison with Pd–Cu. The Tafel analysis reveals that the first charge transfer is the rate-determining step of MEO on Pd@CNWs electrode. The overall MEO reaction orders on Pd@CNWs electrode for CH3OH (ca. 0.23) and OH− (ca. 0.22) reveal that the MEO mechanism maintains unchanged with increasing the CH3OH or OH− concentration at all of the Tafel ranges.